2006
DOI: 10.1007/s11172-006-0289-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3-cyano-4,6-dinitrobenzo[d]isoxazole and its reactions with anionic nucleophiles

Abstract: The action of various anionic O , N , and S nucleophiles on 3 cyano 4,6 dinitro benzo[d]isoxazole mostly resulted in regiospecific nucleophilic substitution for the nitro group in position 4. With an excess of an nucleophilic reagent, the nitro group in position 6 was also replaced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Chemical shifts (δ) are given from Me 4 Si. All the samples for NMR spectroscopy were prepared in DMSO d 6 . IR spectra were recorded on a Specord M 80 spectrometer in KBr pellets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical shifts (δ) are given from Me 4 Si. All the samples for NMR spectroscopy were prepared in DMSO d 6 . IR spectra were recorded on a Specord M 80 spectrometer in KBr pellets.…”
Section: Methodsmentioning
confidence: 99%
“…However, in case of highly electrophilic 3 R 4,6 dinitrobenzo[d]isox azoles (R = CN and CH=NOMe), 6 NO 2 group can also be substituted upon treatment with thiols. 6 As to 2 aryl 4,6 dinitroindoles, to date, there is no information on substitution of the nitro group in these compounds.…”
mentioning
confidence: 99%
“…As an example, 5a reacts readily with thiophenoxide anion (PhS -) at room temperature in N-methylpyrrolidone (NMP) to afford the S N Ar products arising from the successive displacements of the 4-NO 2 and 6-NO 2 groups (Scheme 6). 35 In the same solvent, the temperature must be raised to 50 • C to achieve the S N Ar displacement of a first NO 2 group and to 150 • C to complete the substitution of a second NO 2 group of TNB (Scheme 7). 36, 37 Similarly, the substitutions of the NO 2 groups of 5a by phenoxide (PhO -) and azide (N 3 -) anions take place under much smoother experimental conditions than the displacements of the NO 2 groups of TNB.…”
Section: S N Ar Reactivity Of 5amentioning
confidence: 99%
“…It is known that dinitro-substituted benzoannulated five-membered heterocyclic systems  phthalimides, benzo[ b ]furans, indoles, 2a,b benzo[ b ]thiophenes, benz[ d ]isoxazoles, indazoles, benz[ d ]isothiazoles  undergo selective nucleophilic displacement of a nitro group adjacent to a ring fusion point ( peri -nitro group) with O-, N-, and S-nucleophiles. On the other hand, we recently demonstrated that with 1,3-dinitrodibenz[ b , f ][1,4]oxazepine-11(10 H )-one just the opposite occurs; the nonadjacent nitro group ( para -nitro group) is displaced with O- and S-nucleophiles (Scheme ).…”
Section: Introductionmentioning
confidence: 99%